(untitled) (International Journal of Engineering and Computer Science, 2014)
A lot of sophisticated problems we have to face during the security of RFID credit card. In this paper, author using a new approach to make RFID credit card more secure. The main objective of this paper is to provide a method along with encryption and digestion of incoming and outgoing data to RFID credit card. In this paper we presents a new cryptographic approach to exclude the repetitive terms in a message, when it is encrypted and digest [1], so that it is not easy for any adversary to retrieve or predict the original message from the encrypted message. . By using cryptographic approach, we can improve the security by encrypting the plain text data to cipher text data. If we individually using Caesar cipher substitution and cryptographic hash function, then obtained cipher text is easy to crack. I proposed a perspective approach on combination of techniques substitution and digestion. We can eliminate the fundament weakness by combining Caesar cipher with cryptographic hash function technique.